Importance of cone-beam computed tomography (CBCT) in the preevaluation of surgical removal of an impacted canine, premolar and supernumerary tooth - Omed Shafiq Hamaamin; Mutan Hamdi Aras; Mustafa Ozturk; Ahmet Mete (Genius Journals, 2022)
Impacted teeth could be defined as unsatisfactory tooth eruption at its suitable position. Mostly impacted teeth are wisdom teeth, and after followed by upper canine and lower premolar, respectively. During and after removal of impacted teeth, some complications may be seen such as damage to adjacent teeth, nerve damage, teeth/root escape, maxillary sinus, and nasal base perforation. Proper radiographic evaluations have great interest to eliminate these complications. Conventional radiograph in dentistry such as periapical, occlusal, cephalometric and panoramic radiographs(OPG) provide only(2D) examination. Thus, they provide limited information about the anatomical structures, size, and location of any problems. Also, there are many disadvantages of (2D) imaging methods such as cross-bite, magnification, distortion of images, and perspective problems. Due to insufficiency of (2D) imaging methods, a novel method named conebeam computed tomography (CBCT), which is specially developed to use in head and neck imagines. CBCT has several advantages including low radiation dose, faster scan, accurate precise evaluation, lesser artifact, and magnification. In our study, in the preevaluation of 108 impacted canines, premolar and supernumerary teeth, OPG and CBCT images of 70 patients were assessed and resulting data were compared. In this study we confirm the importance of CBCT evaluation before the surgical removal of impacted teeth in jaws, we concluded that in the removal of regarding teeth together with the OPG, CBCT imaging is a necessity not an option in today's technology
Keywords: CBCT; 2D; Panoramic radiograph; Impacted teeth